2018
DOI: 10.18203/issn.2454-5929.ijohns20185060
|View full text |Cite
|
Sign up to set email alerts
|

Dimensions and morphology of the sinus tympani: an anatomical study

Abstract: <p class="abstract"><strong>Background:</strong> The sinus tympani is a deep pocket of varying dimensions and shape situated in the retrotympanum. The sinus tympani lies medial to the facial nerve. Hence surgical access is difficult. This area is frequently involved in chronic otitis media attico antral type. Removal of disease from this area is difficult leading to cholesteatoma recidivism. The anatomy has been well described in literature. Its dimensions and morphology has not been describe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 6 publications
1
1
0
Order By: Relevance
“…Our study showed that dimensions of the tympanic sinus were highly variable. Both the width and depth of the sinus tympani were measured in numerous studies and in most of them the measurements are consistent with those in our series [ 1 , 3 , 6 , 7 , 9 , 13 , 18 , 20 – 23 , 26 ].…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…Our study showed that dimensions of the tympanic sinus were highly variable. Both the width and depth of the sinus tympani were measured in numerous studies and in most of them the measurements are consistent with those in our series [ 1 , 3 , 6 , 7 , 9 , 13 , 18 , 20 – 23 , 26 ].…”
Section: Resultssupporting
confidence: 91%
“…Basing on the measurements in the current study, the tympanic sinus has a trough-shape; the middle part has the narrowest and deepest dimensions. Wang et al classified ST into three categories: the cup-shaped, the pear-shaped and the boot-shaped, the last one was presented only in patients 2.6 (0.9-6.1) Baklaci et al [3] 2019 HRCT -1.41 ± 0.68 (0.20-3.00) Bekci et al [4] 2020 3D CT --ST volume rise with petrous bone pneumatization Cheita et al [6] 2010 Cadaver 2.00 (1.24-2.76) 2.74 (0.5-6.2) Chen et al [7] 2005 HRCT 1.98 (± 0.71) 2.25 (± 0.91) Donaldson et al [9] 1970 Cadaver -3.75 Kumar et al [13] 2019 Cadaver 1-3 (mean 2.2) 5 (mean 1.72) Mazziotti et al [18] 2006 CT 2.50 (1.5-3.2) 3 (2.3-4.8) Niemczyk et al [20] 2003 Cadaver 2.23 (1.0-3.5) oval Ozturan et al [22] 1996 Cadaver 1.49 (0.49-3.87) 2.06 (± 0.60) Parlier-Cuau et al [23] 1998 HRCT -2.7 (1-9) Saito et al [26] 1971 Cavader 0.96-3.22 (mean 2.14) 2.93 (0.61-5.87) Wang et al [29] 2015 3D HRCT --Cup-shaped, the pear-shaped and the bootshaped with congenital aural atresia [29]. In the literature, the shape of sinus tympani was also described as oval [20] Nitek et al described in most cases the tympanic sinus as elliptical in shape and its long diameter lies in the vertical plane [21].…”
Section: Shapementioning
confidence: 99%